Incidente de resolução de demandas repetitivas: meios de uniformização da jurisprudência no Direito Processual Civil Brasileiro - Ferrari Neto, Luiz Antonio (2012)
Using the comparative and inductive methods and the research to the legislation, doctrine and jurisprudence, we analyse the incident of resolution of repetitive demands, institute that is under discussion at academia and Senate, because of the proposal submitted to the Senate by the draft of the Civil Procedure Law Code Project. At first, aiming to contextualize the procedural science, we will bring the current situation with the problematic of its constant search of the cessation of the slowness of the judiciary, aggregating the constitutionalization of the procedural law, its reforms in the intent to accelerate the delivery of the jurisdictional activity and the problem of the growing necessity to demand justice because of the massification of the legal relations. In a second step, by means of analysing the Brazilian institutes that has the objective of standardization the interpretation and application of the norms, we will treat about the importance of the jurisprudence and the necessity of obeying the precedents of the courts, which we will try to demonstrate that this necessity has always been present in the actual Civil Procedural Code since its beginning, but despite the tendency to follow precedents, unlike the countries of the common law system, the Brazilian practise seek to ignore the factual peculiarities to utilize the earlier judgements in an abstract way, which turns out, sometimes, distorting the interpretation drawn up by the courts. In the third step we will analyse the proposal to include the new institute under the Project of the Civil Procedure Code, named incident to solve repetitive demands, in which we will compare it to another institutes existent in the foreign law and also to institutes that we have in the actual Brazilian law to, from there, checking out the similarities and differences, we could be able to delve in to the nature, competence, procedure and expected results, exposing our opinion about topics that could be improved